2014 IEEE International Conference on Big Data (Big Data) 2014
DOI: 10.1109/bigdata.2014.7004286
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the veracity of event detection on social media networks through user trust modeling

Abstract: With the success and ubiquity of large scale, social media networks comes the challenge of assessing the veracity of information shared across them that inform individuals about emerging real-world events and trends. We propose a veracityassessment model for information dissemination on social media networks that combines natural language processing and machine learning algorithms to mine textual content generated by each user. Large scale social media networks (such as Twitter and Facebook) are considered dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…The authors have demonstrated that large-scale social media networks exhibit the five Vs of "big data" and can serve as a viable source of real-time knowledge extraction though data mining [16,17].…”
Section: Big Data Frameworkmentioning
confidence: 99%
“…The authors have demonstrated that large-scale social media networks exhibit the five Vs of "big data" and can serve as a viable source of real-time knowledge extraction though data mining [16,17].…”
Section: Big Data Frameworkmentioning
confidence: 99%
“…Data veracity is becoming a research hotspot of big data and there have been many related studies in the literature [2,4,10,16,20,15]. For example, Kepner et al [10] introduced a new technique called Computing on Masked Data (CMD) to improve data veracity while allowing a wide range of computations and queries to be performed with low overhead by combining efficient cryptographic encryption methods with an associative array representation of big data.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Kepner et al [10] introduced a new technique called Computing on Masked Data (CMD) to improve data veracity while allowing a wide range of computations and queries to be performed with low overhead by combining efficient cryptographic encryption methods with an associative array representation of big data. Bodnar et al [4] proposed a veracity assessment model for information dissemination on social media networks that combines natural language processing and machine learning algorithms to mine textual content generated by each user. Sanger et al [20] introduced two veracity research branches emerging from the combination of the terms of interest, namely Big Data for Trust and Trust in Big Data.…”
Section: Related Workmentioning
confidence: 99%
“…The U.S. Outpatient Influenza-like Illness Surveillance Network (ILINet) collects information on patient visits to health care providers for influenza-like illness in all 50 states, Puerto Rico, the District of Columbia and the U.S. Virgin Islands, reporting more than 30 million patient visits each year [27]. ILINet provides information through the Centers for Disease Control and Prevention (CDC) 5 , in the form of weekly influenza infection rates across all the geographical regions in the United States.…”
Section: Cutting-edge Solutions For Disease Detectionmentioning
confidence: 99%
“…Online communities generate more than 2.5 quintillion (10 18 ) bytes of data each day [42,5]. A large portion of this data is generated through social media services such as Twitter, Facebook, and Google Plus that process anywhere between 12 terabytes (10 12 ) to 20 petabytes (10 15 ) of data each day [1].…”
Section: Introductionmentioning
confidence: 99%